Propuesta De Fortalecimiento Para La Empresa Postres De´Li (2024)
The following business plan is aimed at the company Desserts De’Li, which produces and sells desserts in the city of Bogotá with innovative products such as exclusive flavors in the market, through which it seeks to implement innovation processes with new proposals in presentations and in unique experiences. Nowadays desserts are desired by people with distinctive flavors and innovative presentation, and the proposal central is creating a customer experience through personalized service and innovative with the possibility of providing a gastronomic experience where the user has the alternative of making your own dessert or cake depending on the occasion, having at your disposal all the ingredients and personnel are available to guide you in your process and thus achieve a learning and at the same time a satisfaction from consuming what is made.